2015
DOI: 10.1007/s10640-015-9922-0
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Assumptions and Predictions of the Hotelling Model

Abstract: In this paper, we empirically examine whether the assumptions and predictions of the Hotelling model are consistent with patterns observed in data. We consider nonlinear functional forms for the extraction cost and resource demand to develop an empirical Hotelling model with technological progress and stock dependent extraction costs. Using panel data on fourteen nonrenewable natural resources to estimate this empirical Hotelling model, we get qualitatively different results as compared to the related literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…To pursue profit maximization, the result of the competition is that each company tends to concentrate on the market center, namely the principle of minimum differentiation (Hotelling, 1929;Iskakov & Pavlov, 2009). The Hotelling model deals with the competition between the points on the line, which connotes a linear competition (Atewamba & Nkuiya, 2017). However, in reality, many enterprises conduct dynamic competition on a spatial plane, thus it is necessary to extend this model to the spatial plane, such as discussing the conditions for obtaining Hotelling equilibrium in a circular space (Hayashi & Tsuge, 2019).…”
Section: Spatial Competition Of Biopharmaceutical Randdmentioning
confidence: 99%
“…To pursue profit maximization, the result of the competition is that each company tends to concentrate on the market center, namely the principle of minimum differentiation (Hotelling, 1929;Iskakov & Pavlov, 2009). The Hotelling model deals with the competition between the points on the line, which connotes a linear competition (Atewamba & Nkuiya, 2017). However, in reality, many enterprises conduct dynamic competition on a spatial plane, thus it is necessary to extend this model to the spatial plane, such as discussing the conditions for obtaining Hotelling equilibrium in a circular space (Hayashi & Tsuge, 2019).…”
Section: Spatial Competition Of Biopharmaceutical Randdmentioning
confidence: 99%
“…As technology progresses more and more, resources can be acquired (Hart, ). As a consequence, tests of the Hotelling model are typically rejected (Halvorsen and Smith, ; Lin and Wagner, ; Atewamba and Nkuiya, ).…”
Section: Major Examples Of Rent Generationmentioning
confidence: 99%
“…As technology progresses more and more, resources can be acquired (Hart, 2016). As a consequence, tests of the Hotelling model are typically rejected (Halvorsen and Smith, 1991;Lin and Wagner, 2007;Atewamba and Nkuiya, 2017). Ellis and Halvorsen (2002) find that the difference between the price and the marginal cost of resources is mostly due to market power rather than scarcity rents.…”
Section: Nonrenewable Resourcesmentioning
confidence: 99%
“…Slade and Thille (), reviewing roughly the same studies, concluded for the rejection of the basic model by data. Further empirical tests, of specific aspects of Hotelling's model, or of elementary extensions of the basic model, reached the same conclusion (e.g., Hart and Spiro , Gaugler , Atewamba and Nkuiya , Karp ).…”
Section: Introductionmentioning
confidence: 99%